Assessment of Dynamics of Inter-Parameter Concatenation during Exercise Tests - Venskaityte, E.; Poderys, J.; Balagué, N.; Bikulciene, L. (Elektronika ir Elektrotechnika, 2009)
The dynamic system components’ interactions are essential in determining how system functions as a whole. Research based on complex model, which integrates the main functional systems, enables to reveal inter-parameter concatenation and allows indicating new features of body’s fatigability obtained during provocative exercise tests. The analytical method was applied for the assessment of physiological system interactions in different fractal levels by electrocardiogram parameters monitoring and its data sequences analysis. The dynamics of inter-parametric concatenation provide new approach of electrocardiogram data sequences analysis and propose usefulness of the analytical methods in the field of complex systems. Ill. 4, bibl. 11 (in English; abstracts in English, Russian and Lithuanian).